Effectiveness of the delivery of interventions to prevent malaria in pregnancy in Kenya. (December 2016) - Dellicour, Stephanie; Hill, Jenny; Bruce, Jane; Ouma, Peter; Marwanga, Doris; Otieno, Peter; Desai, Meghna; Hamel, Mary; Kariuki, Simon; Webster, Jayne
Abstract Background Coverage with malaria in pregnancy interventions remains unacceptably low. Implementation research is needed to identify and quantify the bottlenecks for the delivery and use of these life-saving interventions through antenatal clinics (ANC). Methods A cross-sectional study was carried out in ANC across nine health facilities in western Kenya. Data were collected for an individual ANC visit through structured observations and exit interviews with the same ANC clients. The cumulative and intermediate systems effectiveness for the delivery of intermittent preventive treatment (IPTp) and insecticide-treated nets (ITNs) to eligible pregnant women on this one specific visit to ANC were estimated. Results Overall the ANC systems effectiveness for delivering malaria in pregnancy interventions was suboptimal. Only 40 and 53 % of eligible women received IPTp by directly observed therapy as per policy in hospitals and health centres/dispensaries respectively. The overall systems effectiveness for the receipt of IPTp disregarding directly observed therapy was 62 and 72 % for hospitals and lower level health facilities, respectively. The overall systems effectiveness for ITNs for first ANC visit was 63 and 67 % for hospitals and lower level facilities, respectively. Conclusion This study found that delivery of IPTp and ITNs through ANC was ineffective and more so for higher-level facilities. This illustrates missed opportunities and provider level bottlenecks to the scale up and use of interventions to control malaria in pregnancy delivered through ANC. The high level of clustering within health facilities suggest that future studies should assess the feasibility of implementing interventions to improve systems effectiveness tailored to the health facility level.